Hepatitis E outbreak in Nepal during 2014 - Gupta, Birendra Prasad; A, Adhikari; B, Chaudhary; KD, Manandhar; SB, Yadav; N, Shrestha; R, Rauniyar; BD, Patel (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
Hepatitis E Virus (HEV) is prevalent in developing country like Nepal. There were many sporadic cases as well outbreak is reported from Nepal. The first epidemic of hepatitis E reported in 1973 at Kathmandu, which affected more than 10,000 people, mostly young adults of the age group 25±8. The disease was associated with high incidence of acute hepatic failure and high mortality among pregnant women. There was a massive outbreak of HEV during 2014 infecting more than 6,000 individual with 11 deaths by hepatitis E in Biratnagar Municipality of Nepal within two month between April-May during 2014 outbreak. The first case of HEV documented in first week of April, 2014 and reached to pick level in last week of April. For this study, serum sample was collected from 526 patients and were subjected for the detection of immunoglobulin M (IgM) classes of antibodies against HEV by indirect (sandwich) enzyme immunoassay. Among the 526 samples, IgM anti-HEV-positive percentage from different age groups were 43.84% for ≥25-≤50, 39.71% for >50 and 32.62% for <25 years of age. Our result shows HEV infection is mostly prevalence among the intermediate age group of population. Only two pregnant women out of 526 were infected with HEV. There was no reported death among the pregnant women during 2014 outbreak.